(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Patient satisfaction greatly determines the quality of hospital services, especially the services provided by nurses. The purpose of this study was to study the relationship between servqual dimensions and the level of patient satisfaction in the inpatient room of Tribrata Bhayangkara Hospital, Bengkulu City. This type of research is an analytic survey method using a cross sectional design with accidental sampling with a total of 119 patient. Data collection using a questionnaire with a likers scale. The results showed that 80.7% of patients stated that they were of good quality and 19.3% of patients stated that they were lack of quality, 16% of patients said they were satisfied and 84% of patients said they were less satisfied, Test showed there were 84% patients expressed less satisfaction. and using the Chi-Square, it was found that there was a significant relationship between the Servqual Dimensions and the Satisfaction Level in the Tribrata Inpatient Room at Bhayangkara Hospital, Bengkulu City with the Weak Category.